Penerapan Program Gemilang (Gerakan Minat Literasi Akademik Gen Z) dalam Meningkatkan Minat Baca pada Mahasiswa Semester Tiga Prodi Manajemen Dakwah Fakultas Dakwah dan Ilmu Komunikasi UIN Imam Bonjol Padang - Husna, Nikmatul (Lembaga Intelektual Muda (LIM) Maluku, 2026)
The purpose of this study is to determine and analyze the effect of the implementation of the Gemilang program (Gen Z Academic Literacy Interest Movement) in increasing reading interest in third-semester students of the Da'wah Management study program, Faculty of Da'wah and Communication Sciences, UIN Imam Bonjol Padang. This study was conducted on students, specifically the third-semester Da'wah Management study program at the Faculty of Da'wah and Communication Sciences, UIN Imam Bonjol Padang. The sample in this study was 60 students using the total sampling technique. Total sampling is a sampling technique when all members of the population are used as samples. This is often done when the population is relatively small, less than 30 people, or research that wants to make generalizations with very small errors. The data analysis technique in this study used a quantitative approach. This analysis aims to determine the partial and simultaneous impact of the Gemilang program (Gen Z Academic Literacy Interest Movement) on increasing reading interest in third-semester students of the Islamic Propagation Management study program. The data analysis methods used in this study included validity and reliability tests, descriptive variable analysis, and simple regression analysis. The results indicate that the Gemilang program (Gen Z Academic Literacy Interest Movement) has a positive and significant effect on reading interest.